Winning the White House, 2004 - Rankin, David M. author. aut Link
XIV, 223 p. 6 illus.
Keywords: What does it take to win the White House? This book helps students understand both the issues and how and why people vote for one candidate. After discussing the dynamics of the primary campaigns, the authors examine three broad sets of issues that play a key role in voting: foreign policy, domestic policies, and the culture wars. This sets the foundations for an examination of regional similarities and differences in voting patterns, as the varying salience and valence of issues-whether general or specific-is explored across and within regions. Special attention is paid to battleground states. Drawing on concepts from political science, this book advances students' understanding both of the field and the phenomenon.